INTERACTION OF ETHANOLAMINES WITH COPPER(II) ACETATE MONOHYDRATE - T. J. Atamuratov; S. N. Jabbarbergenova; A. A. Orazbaeva (Modern American Journals, 2026)
Ethanolamines possess biological activity and also function as growth-promoting agents for plants. Copper(II) acetate monohydrate is known to exhibit fungicidal activity against root rot diseases of agricultural crops. A number of studies have been devoted to the interaction of ethanolamine with organic and inorganic salts; however, its interaction with copper(II) acetate monohydrate and the fungicidal activity of the complexes obtained on this basis have remained largely unexplored. Based on experimental investigations, new data were obtained on the solubility and interactions of components in two systems containing water, diethanolamine, triethanolamine, and copper(II) acetate monohydrate. These systems were studied using isomolar methods.
Keywords: Chemical analysis, IR spectroscopic analysis, X-ray phase analysis, thermographic analysis, refractive index, density, viscosity, pH medium